Suicide Prevention Interventions and Their Linkages in Multilayered Approaches for Older Adults: A Review and Comparison - Sakashita, Tomoe; Oyama, Hirofumi (Frontiers in Public Health, 2022)
Multilayered approaches to suicide prevention combine universal, selective, and indicated prevention interventions. These approaches may be more successful in reducing suicide rates among older adults if they use systematic linkages between these layers. This study aimed to examine the effect on suicide rates of the structure of multilayered approaches, and in particular the types of interventions and the linkages between them. We also wished to consider any different effects by gender. A literature search used PubMed and PsycINFO to identify systematic reviews of interventions in this age group. From the reference lists of these articles, we identified controlled studies assessing the impact of a multilayered program on suicide incidence among older adults. We were particularly interested in initiatives linking different kinds of prevention interventions. We found three relevant systematic reviews, and from these, we identified nine eligible studies: seven nonrandomized controlled and two cohort studies. We used a narrative synthesis of these studies to identify five different multilayered programs with different forms of linkages between layers. Two studies/programs involved selective and indicated prevention interventions. One study/program included universal and selective prevention interventions, and the final six studies (two programs) involved linkages between all three layers. We also found that the linkages could be either formal or informal. Formal linkages were professional referrals between levels. Informal linkages included advice from professionals and self-referrals. The programs also often involved strong relationships that developed during the program between service users and services or providers. All five programs were associated with reduced suicide incidence among older women in the target groups or communities. Two programs were also associated with a reduction among men. We therefore suggest that it is important to build relationships between levels, especially between selective and indicated prevention interventions, but that these can be both formal and informal. Additionally, to reach older men, it may be important to create systematic methods to involve mental health professionals in the indicated prevention intervention. Universal interventions, especially in conjunction with systematically linked indicated and selective interventions, can help to disseminate the benefits across the community.